A Multi-Experiment Investigation of the Effects Stance Width on the Biomechanics of the Barbell Squat - Jonathan Sinclair; Paul John Taylor; Bryan Jones; Bobbie Butters; Ian Bentley; Christopher James Edmundson (MDPI AG, 2022)
This two-experiment study aimed to explore habitual and manipulated stance widths on squat biomechanics. In experiment one, 70 lifters completed back squats at 70%, 1 repetition maximum (1RM), and were split into groups (NARROW < 1.06 * greater trochanter width (GTW), MID 1.06-1.18 * GTW and WIDE > 1.37 * GTW) according to their self-selected stance width. In experiment two, 20 lifters performed squats at 70%, 1RM, in three conditions (NARROW, MID and WIDE, 1.0, 1.25 and 1.5 * GTW). The three-dimensional kinematics were measured using a motion capture system, ground reaction forces (GRF) using a force platform, and the muscle forces using musculoskeletal modelling. In experiment two, the peak power was significantly greater in the NARROW condition, whereas both experiments showed the medial GRF impulse was significantly greater in the WIDE stance. Experiment two showed the NARROW condition significantly increased the quadriceps forces, whereas both experiments showed that the WIDE stance width significantly enhanced the posterior-chain muscle forces. The NARROW condition may improve the high mechanical power movement performance and promote the quadriceps muscle development. Greater stance widths may improve sprint and rapid change-of-direction performance and promote posterior-chain muscle hypertrophy. Whilst it appears that there is not an optimal stance width, these observations can be utilized by strength and conditioning practitioners seeking to maximize training adaptations.